Undergraduates selection towards islamic banking in dual banking environment: An empirical study - Kadir M.R.A.; Surbaini K.N.; Ramli J.A. (2023)
To plan an appropriate marketing strategy to attract new customers is very importance, especially for Islamic banking in dual banking environment. Islamic banks need to identify the criteria on where potential customers determine their bank selection decision. The study focuses on examining the bank selection criteria being employed by undergraduates, the potential Islamic banking customers. The purpose of this paper are to examine the main factors that influence undergraduates in selecting their bank preference and whether there is a significant different between Muslim and non Muslim undergraduates in selecting their banking in dual banking environment. This study presents primary data collected by self-administered questionnaires involving 250 undergraduates at UNITEN as samples. The criteria are analyzed using factor analysis with varimax rotation, to cluster the criteria into several variables. The result shows that convenience factor and bank appearance played significant role in selection process by Muslim and non-Muslim undergraduates. We also found encouraging result that religious factor is among important criteria preferred by Muslim undergraduates in selecting their bank.